Improving the Teaching Ability of English Teachers on Writing Materials Through Mind Mapping Methods for Class VII. A Students SMP Negeri 4 Kendari - madina madina (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
Abstract The purpose of this study was to improve the teaching skills of English teachers in writing by using the mind mapping method so that students can enhance their learning outcomes in English subjects. This study uses subjects and data sources for class VII. An SMP Negeri 4 Kendari for 2021/2022 with 36 students. The research design used is the flow method from Kemmis and Taggart with a cycle model. They were collecting research data using observation techniques and learning outcomes tests. The data analysis procedure used an interactive analysis model from Melles and Huberman. The results showed that: (1) the percentage and number of students who scored above the KKM were 33 people (91.67%); and (2) students' perceptions of the use of the mind mapping method applied in this study were very positive, most students said they were happy if this strategy was used in presenting English subject matter. The mind mapping method effectively improves student achievement when learning is understood about strategic activities; the teacher guides students who encounter difficulties in the learning process. At the end of the lesson, an evaluation test is given and reflects on learning.